Characterization of fragment size vis-à-vis delay timing in quarry blasts - Yang H.-S.; Rai P. (My University, 2025)
This research investigates the effect of delay timing on fragmentation. The study reveals that delay timing plays crucial role in the fragmentation. The shorter delay timings were found to yield better fragmentation results in comparison to the longer delay timing in strong limestone benches. Additionally, under the existing field conditions, straight V-type firing pattern provided superior fragmentation results. © 2011 Elsevier B.V.